INVESTMENT OPPORTUNITIES: MEASURING THE POTENTIAL OF ISLAMIC COOPERATIVES AND VILLAGE-OWNED ENTERPRISES - Chandra, Yulian Ade; Suyono, Aji Preasetyo; Ayu Kinanti , Kartika (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Indonesia is currently developing a variety of creative economies. The great potential in the Indonesian economy that still needs to be optimized is Village-Owned Enterprises (BUMDes) and Sharia Cooperatives. Besides. This is because Indonesia has 83,971 villages by 2023, a high Muslim population, the average age of the population is productive age, the culture of Indonesian citizens who live socially, the need for high capital sources and the need for micro-investment is still high. This research was conducted to obtain a clear picture of the potential of Islamic cooperatives and BUMDes in Indonesia. The method used in this research is descriptive quantitative method. The data used to examine Islamic cooperatives is sourced from the Financial Services Authority accompanied by case studies. While BUMDes data uses a sample of 632 BUMDes spread throughout Indonesia. The results of this study show that the growth of Islamic cooperatives is visible in terms of assets, market share and turnover. On the other hand, the level of Islamic financial literacy in Indonesian society is also growing rapidly. In addition to sharia cooperatives, BUMdes also have great potential. The development of BUMDes can be measured from the growth of BUMDes' turnover value. Some BUMDes have a turnover of up to tens of billions of rupiah. For the community and government, investing or cooperating in the sharia cooperative and BUMDes sectors is a wise decision. This is because such decisions can provide future profit opportunities while creating a large domino effect for the community and the country.